2015
DOI: 10.18410/jebmh/2015/1067
|View full text |Cite
|
Sign up to set email alerts
|

Awareness About Prescribed Medications and Lifestyle Modification in Patients With Type2 Diabetes Mellitus

Abstract: BACKGROUND: Diabetes mellitus is one of the most common non-communicable diseases in India. It is one of the diseases in which patient self-care has an important role in long-term outcome. Patient self-care directly depends on level of awareness about the disease, especially knowledge regarding prescribed medications. AIMS AND OBJECTIVES: This study was conducted to know the level of awareness about prescribed medications and lifestyle modification in type 2 diabetes mellitus patients. This study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…), fatty foods and to consume more of wheat/millets/ vegetables. 16 Sut Yee Tse et al, reported that 92% were aware of a relationship between DM and periodontal disease. This awareness was not associated with their years of experience, training status and personal oral health behavior.…”
Section: Discussionmentioning
confidence: 99%
“…), fatty foods and to consume more of wheat/millets/ vegetables. 16 Sut Yee Tse et al, reported that 92% were aware of a relationship between DM and periodontal disease. This awareness was not associated with their years of experience, training status and personal oral health behavior.…”
Section: Discussionmentioning
confidence: 99%